Context-Aware Knowledge Graphs Exploratory Search - dos Santos, Veronica; Haeusler, Edward Hermann; Schwabe, Daniel; Lifschitz, Sergio (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2023: Anais do XXXVIII Simpósio Brasileiro de Bancos de Dados, 2023)
The exploratory search approach recognizes that user queries can be incomplete, inaccurate, and ambiguous. This occurs both because of incomplete domain knowledge by the user or due to implicit assumptions about the context. This ongoing research aims to enrich Knowledge Graphs (KG) to support context-aware exploration through expanded queries. We propose a Contextual KG (CKG) definition and schema that characterizes the necessary elements for modeling contextual information and a query-answering approach that retrieves all (contextualized) possible answers.